Anthropologie der Theorie. - Jürgasch, Thomas (Otium., 2017)
The link between leisure and contemplative activity, as paradigmatically developed in Aristotle's Nicomachean Ethics, has a pre- and long post-history reaching into present day philosophy and theology. Aristotle's melding of leisure with theory is explained anthropologically because human nature's capabilities are perfectly realised in a contemplative form of life. The contributions in this volume investigate models of connecting theory and leisure in the history of ideas with regard to the question of an anthropological foundation of theory.